Sex differences in paediatric airway anatomy. Issue 4 (13th March 2020) - Ripoll, Juan G.; Guo, Winston; Andersen, Kylie J.; Baker, Sarah E.; Wiggins, Chad C.; Shepherd, John R. A.; Carter, Rickey E.; Welch, Brian T.; Joyner, Michael J.; Dominelli, Paolo B.
Abstract : New Findings: What is the central question of this study? Are sex difference in the central airways present in healthy paediatric patients? What is the main finding and its importance? In patients ≤12 years we found no sex differences in central airway luminal area. After 14 years, the males had significantly larger central airway luminal areas than the females. The sex differences were minimized, but preserved when correcting for height. Luminal area is the main determinant of airway resistance and our finding could help explain sex differences in pulmonary system limitations to exercise in paediatric patients. Abstract: Cross‐sectional airway area is the main determinant of resistance to airflow in the respiratory system. In paediatric patients (<18 years), previous evidence for sex differences in cross‐sectional airway area was limited to patients with history of pulmonary disease or cadaveric studies with small numbers of subjects. These studies either only report tracheal data and do not include a range of ages or correct for height. Therefore, we sought to assess sex differences in airway luminal area utilizing paediatric patients of varying ages and no history of respiratory disease. Using three‐dimensional reconstructions from high‐resolution computed tomography scans, we retrospectively assessed the cross‐sectional airway area in healthy paediatric females ( n = 97) and males ( n = 128) over a range of ages (1–17 years). The areas of the trachea, left main bronchus, left upper lobe, left lower lobe, right main bronchus, intermediate bronchus and right upper lobe were measured at three discrete points by a blinded investigator. No differences between the sexes were noted in the cross‐sectional areas of the youngest (ages 1–12 years) patients ( P > 0.05). However, in patients ≥14 years the cross‐sectional areas were larger in the males compared to females in most airway sites. For instance, the cross‐sectional size of the trachea was 25% (218 ± 44 vs . 163 ± 24 mm 2, P < 0.01) larger in males vs . females among ages 13–17 years. When accounting for height, these sex differences in airway areas were attenuated, but persisted. Our results indicate that sex differences in paediatric airway cross‐sectional area manifest after age ≥14 years and are independent of height. Abstract :